PERSEPSI PETERNAK SETELAH MENGADOPSI VAKSINASI PMK ( PENYAKIT MULUT & KUKU ) PADA SAPI BALI DI DESA BULO WATTANG KECAMATAN PANCARIJANG KABUPATEN SIDENRENG RAPPANG: FARMER’S PERCEPTION AFTER ADOPTING FMD (FOOT AND MOUTH DISEASE) VACCINATION ON BALI CATTLE IN BULO WATTANG VILLAGE, PANCARIJANG DISTRICT, SIDENRENG RAPPANG REGENCY - Nurhafizah, Alya; Nugraha, Angga; Mansur, Musdalifa (Tropical Animal Science, 2025)
This study aims to determine the perception of farmers after adopting Foot and Mouth Disease (FMD) vaccination in Bali cattle in Bulo Wattang Village, Pancarijang District, Sidenreng Rappang Regency. This study uses a descriptive quantitative approach. Data were obtained through observation, interviews, questionnaires, and documentation. The research sample consisted of 35 farmers selected purposively. The results showed that farmers' perceptions of FMD vaccination were relatively high, especially in terms of benefits and motivation. However, limitations were still found in the skills of implementing vaccination independently and the availability of supporting facilities. Farmers' awareness of the importance of vaccination is quite good, but its technical implementation is still very dependent on the government and extension workers.